Cloudids: Cloud Intrusion Detection Model Inspired By Dendritic Cell Mechanism - Azuan Ahmad; Norbik Bashah Idris; Mohd Nazri Kama (International Journal of Communication Networks and Information Security (IJCNIS), 2024)
Cloud Computing Security is a new era of computer technology and opens a new research area and creates a lot of opportunity of exploration. One of the new implementation in Cloud is Intrusion Detection System (IDS).There are problems with existing IDS approach in Cloud environment. Implementing traditional IDS need a lot of self-maintenance and did not scale with the customer security requirements. In addition, maintenance of traditional IDS in Cloud Computing system requires expertise and consumes more time where not each Cloud user has. A decentralized traditional IDS approach where being deployed in current Cloud Computing infrastructure will make the IDS management become complicated. Each user's IDS will not be the same in term of type and configurations and each user may have outdated signatures. Inter VM's communication also become a big concern when we implementing Cloud Computing system where communication between Clouds are not monitored and controlled by the traditional IDS. A specific IDS model for Cloud computing is required to solve these problems. In this paper, we develop a prototype of Cloud IDS inspired by Dendritic Cell mechanism. Experiment result proved that Cloud IDS was able to detect any attempt to attack the Cloud environment. The experiments show that the Cloud IDS model based on Dendritic Cell algorithm able to identify and detect novel threat that targeting Cloud environment.